SOLITARY FIBROUS TUMOR OF THE KIDNEY - A. D. Kaprin; A. A. Kostin; N. V. Vorobiev; K. M. Nyushkov; A. O. Tolkachev; A. G. Mouradian (Исследования и практика в медицине, 2015)
A solitary fibrous tumor (SFT) are rare mesenchymal neoplasms and due to the fact of their low occurrence, there are no large-scale researches of this nosology today. The article describes the report of 37‑year old woman with the case of solitary fibrous tumor of the kidney. A laparoscopic radical right nephrectomy was performed. Histological and immunological studies revealed a solitary fibrous tumor of the kidney. The patient did well postoperatively and remains disease-free at the present time.